Novel peptide inhibitor for the Chikungunya virus nsP2 protease: Identification and characterization - Mastalipour, Mohammadamin; Gering, Ian; Coronado, Mônika Aparecida; González, Jorge Enrique Hernández [UNESP]; Willbold, Dieter; Eberle, Raphael Josef (Elsevier, 2025)
Chikungunya virus (CHIKV) is an emerging pathogen affecting populations worldwide, with rapidly increasing infection rates. CHIKV, an arbovirus of the alphavirus genus, is predominantly found in tropical regions and transmitted by Aedes mosquitoes. Climate change has accelerated the global spread of these vectors, leading to outbreaks in non-tropical regions, including parts of Europe. The absence of antiviral therapies and the potential for co-infections with other viruses make CHIKV a significant public health concern. CHIKV replication relies on nsP2 cysteine protease activity to cleave its viral polyprotein into functional nonstructural and structural proteins. Targeting the nsP2 protease represents a promising strategy for antiviral therapy development. In this study, phage display was used to screen a library of peptides for potential binders of the target protease. Biophysical and biochemical analyses of the identified peptides assessed their inhibitory potential. Among the six identified peptides (named as P1–P6), four demonstrated inhibitory effects on the nsP2 protease (nsP2pro). Peptide P1 exhibited the strongest inhibitory effect, with a half-maximal inhibitory concentration (IC50) of 4.6 ± 1.9 µM, and a low cytotoxicity. The secondary structure analysis through CD spectroscopy and homology modelling revealed that P1 adopts an alpha-helical conformation. Finally, molecular dynamics simulations enabled us to investigate the dynamics of the nsP2pro active site and molecular docking was employed to predict the orthosteric binding mode of P1, providing insights into protein-peptide interaction. These findings underscore the potential of peptide P1 as a lead compound for further investigation in the context of CHIKV research.
Keywords: Chikungunya virus; nsP2 protease; Peptide inhibitor